Effects of emerging chemical contaminants on water resources and environmental health - Shikuku, Victor, 1986- (IGI Global, 2020)
""This book explores current issues dealing with the occurrence, toxicology, and abatement of emerging contaminants. It also examines new technologies and developments in sample preparation and detection of contaminants in water resources."-- Provided by publisher.
"Premier Reference Source" -- Cover.
Keywords: Emerging contaminants in water.; Water -- Pollution.; Water -- Purification.; Environmental health.; elektronické knihy; electronic books